Psychological Insights in Marketing Management Strategy: A Qualitative Exploration and Literature Review - Putra, Aditya Halim Perdana Kusuma; Sheyoputri, Aylee Christine Alamsyah (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
This qualitative literature review investigates the integration of psychological insights into marketing management strategy. The research aims to explore the role of emotions, brand personality, social factors, and cognitive processes in shaping consumer behavior and influencing marketing practices. A comprehensive methodology involving systematic literature review and qualitative data analysis is employed. Data collection is conducted through academic databases and relevant sources, employing predefined inclusion and exclusion criteria. The analysis entails coding, categorizing, and synthesizing information to identify emergent themes and patterns. The findings reveal the pivotal role of emotions in consumer decision-making, the significance of brand personality in consumer perceptions, the influence of social factors on consumer behavior, and the prevalence of cognitive processes in decision-making. Emotional engagement, brand storytelling, and leveraging social influence emerge as key strategies for marketers, while understanding cognitive biases informs effective marketing tactics. The study provides valuable insights for marketing management strategy, emphasizing the importance of integrating psychological insights into marketing practices to create meaningful connections with consumers and drive business success.